Knowledge discovery in biomedical data facilitated by domain ontologies - Sidhu, Amandeep; Kennedy, P.; Simoff, S.; Dillon, Tharam S.; Chang, Elizabeth (IGI Global, 2007)
In some real-world areas, it is important to enrich the data with external background knowledge so as to provide context and to facilitate pattern recognition. These areas may be described as data rich but knowledge poor. There are two challenges to incorporate this biological knowledge into the data mining cycle: (1) generating the ontologies; and (2) adapting the data mining algorithms to make use of the ontologies. This chapter presents the state-of-the-art in bringing the background ontology knowledgeinto the pattern recognition task for biomedical data.